Using immunological criteria to predict utilization of soybean proteins by the early-weaned pig - Li, D.F.; Reddy, P.G.; Blecha, Frank; Klemm, R.D.; Nelssen, Jim L.; Goodband, Robert D.; Hancock, Joe D. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
Two trials were conducted to determine the suitability of soybean products for baby pigs. For trial 1, 40 weanling pigs were orally infused with .01 lb/pig/d of either dried skim milk (control), soybean meal (48% CP), soy protein concentrate, extruded soy protein concentrate, or soy protein isolate from d 7 to 12 of age, weaned at 21 d of age, and fed a diet containing the corresponding protein source until d 7 postweaning. Sows were fed a corn-corn gluten meal-based diet supplemented with lysine and tryptophan to avoid exposure of pigs to soybean proteins. All pigs were sacrificed at 28 d of age. In Trial 2, 48 pigs were utilized, with preweaning treatments identical to those in Trial 1 except the soy protein isolate was not used as a treatment. They were fed a diet containing the same protein source for 2 wk postweaning, then fed a common diet with 4% soybean oil and 1.25% lysine for 3 wk. Growth performance was measured. Results indicated that pigs fed diets containing soybean meal had lower villus height and rate of gain than pigs on any other treatments. There were no differences in villus height and crypt depth among soy protein concentrate, extruded soy protein concentrate, and soy protein isolate. In the growth trial, pigs fed the diet containing extruded soy protein concentrate had the highest ADG compared to other soybean products tested. Decreased villus height and increased serum anti-soy IgG titers, coinciding with inferior performance and presence of residual antigenic protein in the digestive tract of baby pigs fed soybean meal, indicate that conventionally processed, commercial soybean meal retain antigens that cause immunological changes in early-weaned pigs.
Keywords: Swine; Piglet; Soybeans; Hypersensitivity; Small intestine; Performance